2003
DOI: 10.1097/00042737-200308000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Non-endoscopic diagnosis of atrophic gastritis with a blood test. Correlation between gastric histology and serum levels of gastrin-17 and pepsinogen I

Abstract: The diagnosis of atrophic gastritis obtained with the blood test panel of S-G-17, S-PGI and H. pylori antibodies is in good agreement with the endoscopic and biopsy findings. The panel is a tool for non-endoscopic diagnosis and screening of atrophic gastritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
141
2
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(164 citation statements)
references
References 13 publications
19
141
2
2
Order By: Relevance
“…These results are similar with what has been reported in many other countries for example Sipponen et al (2002) [18] in Finland; Väänänen et al (2003) [19] in Finland; Pasechnikov et al (2004) [20] in Russia; Cavallaro et al (2004) [21] in Italy respectively reported the accuracy, sensitivity and specificity of the GastroPanel test as (91%:89%:93:%); (81%:79%:91%); (84%:79%:96%) and (96%:78%:98%). There was however, a significant difference in the diagnosis of atrophic antrum gastritis between the GastroPanel and histology (p < 0.01).…”
Section: Discussionsupporting
confidence: 93%
“…These results are similar with what has been reported in many other countries for example Sipponen et al (2002) [18] in Finland; Väänänen et al (2003) [19] in Finland; Pasechnikov et al (2004) [20] in Russia; Cavallaro et al (2004) [21] in Italy respectively reported the accuracy, sensitivity and specificity of the GastroPanel test as (91%:89%:93:%); (81%:79%:91%); (84%:79%:96%) and (96%:78%:98%). There was however, a significant difference in the diagnosis of atrophic antrum gastritis between the GastroPanel and histology (p < 0.01).…”
Section: Discussionsupporting
confidence: 93%
“…Various studies in different populations demonstrated different levels of serum PGI, PGII and the PGI:II ratio (Table I) (19)(20)(21)(22)(23)(24). Serum PG concentrations measured in certain areas of Asia appear to be higher than those in Western countries.…”
Section: Introductionmentioning
confidence: 99%
“…thus, a full understanding of the molecular mechanism of carcinogenesis and identification of biomarkers for the early diagnosis and effective treatment of human GC are crucial. Although several serum biomarkers have been researched as new invasive tools for screening GC (6)(7)(8)(9), these serum tests are not available as screening or surveillance tests due to their low specificity and sensitivity (9). Biomarkers derived from tumor tissues may provide higher sensitivity and specificity than those from serum (10), yet tissue specimens must be obtained by invasive means involving endoscopy and biopsy.…”
Section: Introductionmentioning
confidence: 99%